2014
DOI: 10.3109/14767058.2014.986649
|View full text |Cite
|
Sign up to set email alerts
|

Reliable and powerful laboratory markers of cobalamin deficiency in the newborn: plasma and urinary methylmalonic acid

Abstract: Plasma MMA and urinary MMA B12 are the most robust markers of cobalamin deficiency. As a non-invasive method, urinary MMA is a sensitive method in demonstrating cobalamin deficiency in the newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…There are, however, limited prospective data on maternal vitamin B 12 status during pregnancy and its association with infant vitamin B 12 status—particularly among adolescents—to compare findings. Evidence from studies in adult pregnant women have reported significant correlations between maternal vitamin B 12 status during pregnancy and their infants [19,23,24,26,29]. Few prospective analyses to date have considered potential confounders of these associations in multivariate analyses [25,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are, however, limited prospective data on maternal vitamin B 12 status during pregnancy and its association with infant vitamin B 12 status—particularly among adolescents—to compare findings. Evidence from studies in adult pregnant women have reported significant correlations between maternal vitamin B 12 status during pregnancy and their infants [19,23,24,26,29]. Few prospective analyses to date have considered potential confounders of these associations in multivariate analyses [25,28].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal vitamin B 12 concentrations during pregnancy are thought to predict fetal [18,19,20,21,22,23,24,25,26] and early infant [25,27,28,29] vitamin B 12 status. Previous cross-sectional studies in Norway, Turkey, Germany, United Kingdom, Serbia, and Brazil have noted a significant correlation between maternal and infant vitamin B 12 status at delivery [18,20,21,22,30,31,32,33]; however, in one study in Belgium, maternal and infant vitamin B 12 concentrations were not significantly correlated [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because serum B12 assays provide an estimate of total B12 rather than direct evidence of metabolic utilisation, it is not possible to confidently exclude B12 deficiency when results fall in the indeterminate range of 125‐250 pmol/L. Serum concentrations of homocysteine (Hcy) and the cobalamin biomarker, MMA become increased in B12‐deficient subjects and they are, therefore, considered specific markers of B12 deficiency 21 …”
Section: Diagnosismentioning
confidence: 99%
“…Indeed, borderline cobalamin status in pregnant women can be associated with an increased risk of acquired newborn B12 deficiency, and cobalamin alone may not be sufficient to diagnose deficiency among them, which is why MMA tests are required [42]. Last but not least, we are aware that there are more reliable markers of cobalamin deficiency, namely methylmalonic acid (e.g., MMA), which can be used; therefore, further analysis of our group of patients using levels of MMA would be certainly needed and widely beneficial [15,43,44]. The main strength of the study is the relative balance between the study groups, with only a slightly higher number of children aged 0-3 years in the VN group and no significant differences in sex, height, weight, or BMI.…”
Section: Discussionmentioning
confidence: 99%